INOVASI PELAYANAN PUBLIK ELEKTRONIK SISTEM APLIKASI BANTUAN KOTA (SABAKOTA) KOTA TANGERANG - Latifah Latifah; Adie Dwiyanto Nurlukman; Ahmad Chumaedy; Arif Ginanjar Suryatman (Universitas Bina Taruna Gorontalo, 2023)
Sabakota is an electronic Tangerang City Assistance Application System) is an innovation of the Tangerang City Communication and Informatics Service aimed at preventing problems related to the transparency of grant funds and social assistance and providing convenience for grant applicants. The purpose of this study is to describe Sabakota's electronic Public Service Innovation. This research uses qualitative descriptive research. The research focus uses the theory of innovation success factors according to Cook, Mattews and Irwin consisting of Leadership, Management / Organizatin, Risk Management, Human Capital and Technology. The results of this study show that Sabakota's electronic service innovation has been running quite well even though in its implementation there are obstacles. This is evidenced by analysis using innovation success factors, among others. The leadership factor held by the person in charge of Sabakota's service innovation has shown its role, responsibility and commitment well. Management/Organization factors related to policy strategies and network improvement have been well done. The Risk Management factor shows that there are still obstacles in the difficulty of changing the habit of grant applicants to apply toelectronic systems, low digital literacy of the community, as well as obstacles in technical implementation, the Human Capital Factor shows that in terms of the quality of Human Resources has been adequate but still lacking in terms of quantity.